Interregional and intersectoral interaction of digital economy in China - Ma, Zhong; Niu, Xingxing; Ma, Weijing; Kang, Yanxia; Xie, Weiwei (Frontiers in Environmental Science, 2023)
With the continuous advancement of the integration of the world's digital economy, the economic development of various regions has become increasingly interdependent. However, the interregional interactions of digital industries have yet to be further elucidated. Here, based on the Multi-Regional Input-Output (MRIO) model, we take China for example, and analyze the impact of digital industries on the economy from the industrial and regional. At the industry level, we discuss the economic spillover relationship between the digital industry and the three traditional industries, and analyzes the spatial and temporal differentiation in the inter-industry spillover status of China's 30 provinces; at the regional level, we discuss the digital industrial economic spillover links and spillover states. The results show that: (1) The self-generating ability within the digital industry sector is the most significant factor influencing the industrial growth of China's digital economy, followed by the interrelated effect between industry sectors, while the inter-industry feedback effect has a weak impact on the economic system. (2) There is a clear gap in the economic spillover capacity of the digital industry in 30 provinces, and the overall performance is decreasing in the eastern, central and western regions. (3) The intra-regional multiplier effect of digital industry shows a slowly decreasing trend, and the intra-regional digital economic spillover-feedback effect shows a growing trend. At the same time, the inter-regional digital economy interaction tends to decay in distance, indicating that regional accessibility has a significant impact on the inter-regional spillover effect.